Simulation of complex thermal physical systems with the use of a fuzzy logic - Shevchenko, A. I.; Minenko, A. S.; Gololobova, A. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
The Stephan problem is investigated. The approximate solution is constructed. The control over the process of crystallization with using a fuzzy logic is realized.